Development of Haber Media Based on Illustrated Number Letters to Early Childhood Cognitive Abilities - Fadhillah Afifah; Usman Bafadal; Lukman Lukman (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2022)
This study aims to describe the level of needs, determine the design of Haber's media development in developing AUD cognitive abilities, and determine the effectiveness and practicality of developing Haber's media and guidebooks in developing AUD cognitive abilities. This type of research includes R&D development research. Data collection techniques in this study were conducted using interviews, observations, and questionnaires. The subjects of this study were four teachers in group B. The methods of quantitative and qualitative data analysis. The results show that level of need for Haber's media development is very much needed in developing cognitive abilities in early childhood, the form of the Haber media development design in developing AUD cognitive abilities is designed in the order of preparation of the instrument guidebook for using Haber's media development in developing cognitive skills AUD functional and operational basis, level the practicality and effectiveness of Haber's media development in the development of AUD's cognitive abilities got results from very effective teachers.